Albert Gallatin papers - Gallatin, Albert, 1761-1849.
Correspondence, writings, and notes, relating to such topics as the Treasury Department, the trial of Aaron Burr, U.S. relations with France, the Oregon boundary question, and Gallatin's ethnological work on Indian tribes of Mexico and on Indian languages. Correspondents include Daniel W. Coxe, Thomas Jefferson, Benjamin Lincoln, Thomas L. McKenney, Caesar A. Rodney, and William Short.
Diplomat and U.S. secretary of the treasury.
Collection material in English.
Keywords: United States. -- Department of the Treasury; Burr, Aaron, -- 1756-1836.; France -- Foreign relations -- United States; United States -- Foreign relations -- France; Oregon -- Boundaries; Indians of Mexico; Ethnology; Indians -- Languages; Coxe, Daniel W. -- 1769-1852.; Jefferson, Thomas, -- 1743-1826.; Lincoln, Benjamin, -- 1733-1810.; McKenney, Thomas Loraine, -- 1785-1859.; Rodney, C. A. -- 1772-1824.; Short, William, -- 1759-1849.; Cabinet officers; Diplomats